Penerapan Media Pembelajaran 2 Dimensi Berbasis Montessori Untuk Meningkatkan Hasil Belajar Mata Pelajaran IPA Kelas 3 Di SDN Kalisalam 1 Kabupaten Probolinggo - ., Siti Kholifah S.M.W; ., Ludfi Arya Wardana; ., Shofia Hattarina (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Based on the results of the research data, it shows that the learning activities of students in class 3 at the beginning of the meeting can be categorized as low and the teaching materials used by class 3 teachers are very conventional, less effective and the teacher still uses lecture, discussion and assignment methods. based on some of the problems that occurred in the research, the researchers decided to make observations at Kalisalam 1 Elementary School regarding the Application of Montessori-based 2-dimensional learning media with the aim of knowing how Montessori-based 2-dimensional learning media can improve learning outcomes in science learning in class 3 students of Kalisalam Elementary School 1 Probolinggo Regency. The type of research used was Classroom Action Research (CAR) with the subjects in this study being grade 3 students at SDN Kalisalam 1, Probolinggo Regency, consisting of 28 students, namely 10 male students and 18 female students. The data collected in this study were student activities, student learning outcomes, observation, interview, test, and documentation during learning activities. Data analysis used by researchers is descriptive qualitative, namely data obtained from an analysis of student activities during teaching and learning activities and comparing student learning outcomes in the initial conditions before improvement with learning outcomes obtained after taking action in the first cycle. Based on the details of the results of the implementation of the action as much as 2 cycles in science learning. It can be concluded that learning science on the subject of weather, climate, season and its influence on the lives of living things using 2-dimensional montessori-based learning media can improve learning outcomes with mastery learning by 79.00% in cycle 2 where this figure is very significant when compared to the level of learning completeness in cycle 2. 1 which is 66.6%.